Forming first impressions of children: the role of attention‐deficit/hyperactivity disorder symptoms and emotion dysregulation. (30th October 2017) - Lee, Christine A.; Milich, Richard; Lorch, Elizabeth P.; Flory, Kate; Owens, Julie Sarno; Lamont, Andrea E.; Evans, Steven W.
Abstract : Background: Previous research on peer status of children with attention‐deficit/hyperactivity disorder (ADHD) has focused on already‐established peer groups, rendering the specific social behaviors that influence peers' initial impressions largely unknown. Recently, theorists have argued that emotion dysregulation is a key aspect of ADHD, with empirical work finding relations between emotion dysregulation and social outcomes. Therefore, the current study focuses on the initial interactions among children varying in ADHD symptoms duringh a novel playgroup, proposing that emotion dysregulation displayed during the playgroup may serve as a possible pathway between ADHD symptoms and peers' initial negative impressions. Methods: Participants were 233 elementary‐age children ranging from 8 to 10 years old ( M = 8.83, 70% male). Parents and teachers rated children's ADHD symptoms and related impairment; 51% of the children met criteria for an ADHD diagnosis. Then, children participated with unfamiliar peers in a three‐hour playgroup that included three structured and two unstructured tasks. After the tasks, children and staff rated each child on social outcomes. Coders unaware of child's diagnostic status watched videos of the groups and rated each child's global emotion dysregulation during each task. Results: Using multiple raters and methods, ADHD severity was associated with more negative peer ratings, through observed emotion dysregulation. Results were consistent for both parent and teacher ratings of ADHD severity as well as for both peer ratings of likeability and staff ratings of perceived peer likeability. Conclusions: When focusing on improving peers' initial impressions of children with ADHD symptoms, emotion dysregulation may be a valuable target for intervention.